1999
DOI: 10.1002/cjce.5450770113
|View full text |Cite
|
Sign up to set email alerts
|

The CO‐catalyzed conversion of H2S to H2 + sulfur part 2. The thermal decomposition of COS

Abstract: Research and Technology Branch, Alberta Energy, Edmonton, AB T5K 2G6, CanadaThe pyrolysis of COS has been studied over the temperature range 300 to 750°C using a variety of catalysts. The observed product distribution confirmed that two parallel reaction paths: 2 COS -+ 2 CO + S, (2) and 2 COS -+ CO, + CS, (4) are involved in the decomposition. The decomposition yield increased with rising temperature, accompanied with a shift in selectivity. At temperatures lower than -700°C the disproportionation reaction 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…Despite reaction ( 46) is considered as the main obstacle limiting or even preventing this scheme from having a real application, this process was revamped and optimized by Cimini et al (1997), who proposed a strategy for the elimination of unwanted by-products reducing the process yield. Faraji et al (1999) observed that an accurate choice of temperature can minimize the side reaction (46) which is damped at T>973 K with a favorable selectivity towards reaction (45). Finally, the main issue came from the studies of Gibson and Wachs (2006), who obtained a satisfactory regeneration of CO by catalytic oxidation:…”
Section: Revamping Of Co/cos Cyclesmentioning
confidence: 99%
“…Despite reaction ( 46) is considered as the main obstacle limiting or even preventing this scheme from having a real application, this process was revamped and optimized by Cimini et al (1997), who proposed a strategy for the elimination of unwanted by-products reducing the process yield. Faraji et al (1999) observed that an accurate choice of temperature can minimize the side reaction (46) which is damped at T>973 K with a favorable selectivity towards reaction (45). Finally, the main issue came from the studies of Gibson and Wachs (2006), who obtained a satisfactory regeneration of CO by catalytic oxidation:…”
Section: Revamping Of Co/cos Cyclesmentioning
confidence: 99%
“…Certainly, other routes cannot be excluded, for example, via Eqs. (9) and (10), which may also be very important [6,[14][15][16][17][18][19][20][21].…”
Section: Thermodynamic Equilibrium Analysismentioning
confidence: 98%
“…But they didn't advance the explanation [19,21]. In order to find out the truth behind the similarity or the divergence of catalytic performance during the reactions between CO 2 and H 2 S, the characterizations on the physico-chemical properties of the catalysts were implemented in the present study.…”
Section: Catalytic Performance Of Other Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Claus process is facing the danger of extinction because of many reasons such as (i) underutilization of valuable hydrogen source, (ii) requirement of highly precise air rate control, (iii) the presence of trace sulfur compounds in the spent air, etc. Several reports can be found in the literature for the production of hydrogen and sulfur from H 2 S gas, through thermal , photochemical , electrochemical , and thermochemical processes . Syngas (H 2 , CO), which has been reported to be produced by pyrolysis of acid gases (H 2 S, CO 2 ), can be used as fuel for gas engines .…”
Section: Introductionmentioning
confidence: 99%